Experimental climate warming alters aspen and birch phytochemistry and performance traits for an outbreak insect herbivore. (3rd February 2015) - Jamieson, Mary A.; Schwartzberg, Ezra G.; Raffa, Kenneth F.; Reich, Peter B.; Lindroth, Richard L.
Abstract Climate change and insect outbreaks are key factors contributing to regional and global patterns of increased tree mortality. While links between these environmental stressors have been established, our understanding of the mechanisms by which elevated temperature may affect tree–insect interactions is limited. Using a forest warming mesocosm, we investigated the influence of elevated temperature on phytochemistry, tree resistance traits, and insect performance. Specifically, we examined warming effects on forest tent caterpillar (Malacosoma disstria) and host trees aspen (Populus tremuloides) and birch (Betula papyrifera). Trees were grown under one of three temperature treatments (ambient, +1.7 °C, +3.4 °C) in a multiyear open‐air warming experiment. In the third and fourth years of warming (2011, 2012), we assessed foliar nutrients and defense chemistry. Elevated temperatures altered foliar nitrogen, carbohydrates, lignin, and condensed tannins, with differences in responses between species and years. In 2012, we performed bioassays using a common environment approach to evaluate plant‐mediated indirect warming effects on larval performance. Warming resulted in decreased food conversion efficiency and increased consumption, ultimately with minimal effect on larval development and biomass. These changes suggest that insects exhibited compensatory feeding due to reduced host quality. Within the context of observed phytochemical variation, primary metabolites were stronger predictors of insect performance than secondary metabolites. Between‐year differences in phytochemical shifts corresponded with substantially different weather conditions during these two years. By sampling across years within an ecologically realistic and environmentally open setting, our study demonstrates that plant and insect responses to warming can be temporally variable and context dependent. Results indicate that elevated temperatures can alter phytochemistry, tree resistance traits, and herbivore feeding, but that annual weather variability may modulate warming effects leading to uncertain consequences for plant–insect interactions with projected climate change.